FAKTOR RISIKO KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL DI PUSKESMAS GUNUNG ANYAR SURABAYA - Deah Oktavita; Novera Herdiani (Sekolah Tinggi Pariwisata Mataram, 2023)
The most common nutritional disorder in pregnant women is Chronic Energy Deficiency (CED). Anemia and Chronic Energy Deficiency (CED) in pregnant women is the main cause of bleeding and infection which are the main factors of maternal death. The purpose of this study was to identify and analyze SEZ factors in pregnant women at the Gunung Anyar Health Center in Surabaya. The design of this study was Quantitative Analytical Observational using a cross sectional approach, the population was all pregnant women who visited during the last 3 months totaling 100 people, the sample in this study was determined by the Lemeshow formula as many as 30 respondents, the sampling technique in this study was Accidental Sampling, Univariate analysis is presented in the form of a frequency distribution and bivariate analysis used is Chi-Square.The results of this study were that there was no relationship between education (p=0.537), there was a relationship between work (p=0.002), there was no relationship between pregnancy spacing (p=1.000), there was a relationship between age (p=0.001), there was no relationship between knowledge (p=0.372).The conclusion is that there is a relationship between work and age, and there is no relationship between education, spacing of pregnancies, and knowledge with Chronic Energy Deficiency in pregnant women. Suggestion To be able to conduct research using variables such as parity, infectious diseases, etc. because there are still many factors associated with the incidence of Chronic Energy Deficiency (CED) in pregnant women